Twenty four hour imaging delay improves viability detection by Tl-201 myocardial perfusion scintigraphy - Koc, Zehra Pinar; Balci, Tansel Ansal; Dagli, Necati (Soc Brasil Cirurgia Cardiovasc, 2013)
Objective: Since twenty-four-hour imaging by Tl-201 myocardial perfusion scintigraphy has been introduced as an effective additional procedure, the aim of this study was to compare this method's result with only rest redistribution procedure in the diagnosis of myocardial viability. Methods: Thirty patients (Seven female, 23 male; mean: 59.8 +/- 10.7, 55.8-63.8 years old) with diagnosis of coronary artery disease were involved in this study. All patients had anamnesis of previous myocardial infarction and/or total occlusion of any main artery in the coronary angiography. Myocardial perfusion scintigraphy with Tl-201 with rest four hour (early) redistribution and 24 hour delayed redistribution protocol were performed to all of the patients. The images were evaluated according to 17 segment basis by an experienced nuclear medicine physician and improvement of a segment by visual interpretation was considered as viable myocardial tissue. Results: Viability was found at 52 segments in the early redistribution images and additional 18 segments in the 24 hour delayed redistribution images on segment basis in the evaluation of 510 segments of 30 patients. On per patient basis, among the 26 patients who had viable tissue, 14 (54%) had additional improvement in 24 hour delayed images. Three (12%) patients had viable tissue in only 24 hour delayed images. Conclusion: Delayed imaging in Tl-201 MPS is a necessary application for the evaluation of viable tissue according to considerable number of patients with additional improvement in 24 hour images in our study, which is restricted to the patients with myocardial infarct.
Atraso de imagem de 24 horas melhora a viabilidade de detecção por cintilografia de perfusão miocárdica Tl-201
Keywords: Vascular diseases; Coronary artery bypass; Coronary artery disease